Posh talk : language and identity in higher education - Preece, Siân, 1960- (Palgrave Macmillan, 2009)
"This is an in-depth study of a group of multilingual students from widening participation backgrounds on a first-year undergraduate academic writing program. The book explores ways in which identity positions emerge in the spoken interaction, with a particular focus on gender"--Provided by publisher.